CAV3 gene sequence variations: National Genome Database and clinics. (28th January 2015) - Stavusis, J.; Inashkina, I.; Jankevics, E.; Radovica, I.; Micule, I.; Strautmanis, J.; Naudina, M. S.; Utkus, A.; Burnyte, B.; Lace, B.
<x xml:space="preserve">Abstract</x> Introduction Caveolinopathies are a group of untreatable, degenerative muscle diseases associated with caveolin 3 (CAV3) gene mutations. Objectives The goal of this study was to characterize the role of the CAV3 gene in patients with limb‐girdle muscular dystrophy, hyperCKemia, cardiomyopathies, as well as utilization of the National Genome Database in clinical applications. Materials and methods We sequenced the coding region and exon/intron boundaries of CAV3 gene in 81 neuromuscular disorder patients, a sample group from the National Genome Database, consisting of 97 individuals with cardiomyopathies, and also random selection of 100 persons. Immunohistochemical staining of muscle biopsy was performed to verify findings in one case, as the setup for the project was to use less invasive molecular biology methods. Results We identified three novel sequence variations (c.183C>G, p.S61R; c.220C>A, p.R74S; c.220C>T, p.R74C) and found evidence that one was associated with hypercreatine kinase‐emia. Two previously reported mutations in families with limb‐girdle muscular dystrophy were found. No mutations were identified in the cohort of patients with cardiomyopathies. Discussion CAV3 gene encodes muscle‐specific protein with dominant negative type of missense mutations in it causing various phenotypes. Our study confirmed CAV3 gene involvement in neuromuscular disorders, but found no evidence in the group of patients with cardiomyopathies. Persons included in the National Genome Database could be screened for late onset Mendelian diseases.